Physical fitness, musculoskeletal disorders and body mass index in transport drivers from Barranquilla, Colombia (2019)
Introduction: Sedentary work activities in urban transport drivers are associated with overweight and obesity, an increase in musculoskeletal discomfort related to work and a decrease in physical fitness. Objective: To determine physical fitness and musculoskeletal discomfort in urban transport drivers from Barranquilla, Colombia, based on their body mass index (BMI). Material and Methods: Cross-sectional study conducted in 231 urban transport drivers. Healthy physical fitness and presence of musculoskeletal symptoms were measured using the AFISAL-INEFC test battery and the Nordic Questionnaire developed by Kuorinka, respectively. Results: There were significant differences between drivers with normal BMI and overweight/obese drivers in abdominal strength and endurance (21.4±8.9 vs. 19.6±8.8 stooped, p=0.04), flexibility (36.1±7.3 cm vs. 33.6±7.1 cm, p=0.02), and aerobic capacity (1537.5±704.8 meters vs. 1249.1±346.6 meters, p=0.0001). Increased frequency of musculoskeletal discomfort was observed in subjects with BMI >25 kg/m2. Conclusions: Overweight and obesity are associated with poor physical fitness and the perception of musculoskeletal discomfort, which has negative implications for the personal and occupational well-being of these workers, generating a burden for companies and the Colombian health system.